Effects of thermal to frequency response function on milling tool using finite element analysis - Muhammad Amirul Anshor, Sapiee @ Muhammad Syafiei (2016)
Chatter is not acceptable because it can increase the cost when the spindle and tool life is shorten as the chatter occur. Thermal error is the significant factors in inducing the accuracy of machine tool. Thermal error compensation is an effective way to reduce the thermal error. The objectives of this study is to determine frequency response function of milling with thermal effect and to investigate the effect of heat on frequency response function. The relationship between the natural frequency and mode shapes of end mill is analyzed. A spindle and end mill is designed and implemented with modal analysis to study the natural frequency and mode shape. The parameter of temperature is set between 0oC until 80oC. The parameter of speed is set between 0 RPM until 20,000 RPM. An analysis setup consists of finite element method simulation modal analysis with thermal and modal analysis with speed. The results of natural frequency and mode shape from modal analysis with thermal and modal analysis with speed are same.